Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1063/1.3700722
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of GaN based light-emitting diodes with a p-InGaN hole reservoir layer

Abstract: A p-type InGaN hole reservoir layer (HRL) was designed and incorporated in GaN based light-emitting diodes (LEDs) to enhance hole injection efficiency and alleviate efficiency droop. The fabricated LEDs with p-type HRL exhibited higher light output power, smaller emission energy shift and broadening as compared to its counterpart. Based on electrical and optical characteristics analysis and numerical simulation, these improvements are mainly attributed to the alleviated band bending in the last couple of quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Table 1, from which we can see the effective valence band barrier heights of the quantum barriers for LED II is smaller than those for LED I. It has been reported that the effective valance band barrier height for the p-EBL can be reduced by employing GaN/InGaN as the last quantum barrier, hence promoting the hole injection into InGaN/GaN MQWs [27,28]. However, as found in this work, the same physical principle can be applied to the case when the n-type In 0.10 Ga 0.90 N layer is inserted between n-GaN layer and InGaN/GaN MQW region.…”
Section: Resultsmentioning
confidence: 97%
“…Table 1, from which we can see the effective valence band barrier heights of the quantum barriers for LED II is smaller than those for LED I. It has been reported that the effective valance band barrier height for the p-EBL can be reduced by employing GaN/InGaN as the last quantum barrier, hence promoting the hole injection into InGaN/GaN MQWs [27,28]. However, as found in this work, the same physical principle can be applied to the case when the n-type In 0.10 Ga 0.90 N layer is inserted between n-GaN layer and InGaN/GaN MQW region.…”
Section: Resultsmentioning
confidence: 97%
“…Meanwhile, it has been reported that the hole injection efficiency is improved by tailoring the last quantum barrier (LQB) in InGaN/GaN light-emitting diodes without sacrificing the electrons confinement capability. [15][16][17][18][19][20][21] For examples, inserting a p-InGaN layer before the p-EBL, [15][16][17][18] applying a p-InGaN/GaN superlattice as the LQB, 19 p-type doping LQB, 20 and thinning the LQB 21 have previously been proposed. However, all of these approaches have to deal with the Mg back-diffusion to the last few QWs.…”
mentioning
confidence: 99%
“…In recent years, people have proposed some possible physical mechanisms for efficiency droop such as poor hole injection efficiency [4], electron leakage [5], polarization effect [6], junction heating [7], carrier delocalization [8], the quantum confined stark effect (QCSE) [9], and the Auger recombination [10]. Among the numerous factors, the severe electron leakage and the poor hole injection efficiency are perceived as a key factor for this issue which has been identified by Wang et al [11] In order to overcome the problem, scientists have proposed various effective structures from many point of views, such as the usage of AlGaN barriers [12], InGaN-AlGaN-InGaN barriers [13], staggered quantum wells (QWs) [14], graded electron blocking layer (EBL) [15], AlGaN/GaN superlattice EBL of gradual Al mole fraction [16] and hole reservoir layer [17] In this work, the performance is improved mainly by adjusting the last quantum barrier of LEDs. Recently, Kuo and co-workers [18] proposed the structure with p-doped last barrier to improve the optical performance of the GaN LEDs basing on conventional LED structures.…”
Section: Introductionmentioning
confidence: 99%